Strengthening Village Licensing Services Through Open and Accountable Minimum Service Standards in Sindangheula Village, Serang Regency - Diki Okta Dwi Putra; Rila Kusumaningsih; Ferina Ardhi Cahyani; Ahmad Rayhan (Probono and Community Service Journal, 2026)
The provision of public services at the village level, particularly in licensing procedures, often faces challenges related to legal certainty, transparency, and potential maladministration. This article describes efforts to strengthen state administrative law through the implementation of Minimum Service Standards (SPM) based on Minister of Home Affairs Regulation Number 59 of 2021 in Sindangheula Village, Serang Regency. The objective of this activity is to enhance the legal understanding of village officials and the community regarding standardized service benchmarks, thereby establishing licensing procedures that are transparent, accountable, and free from illegal levies. The method employed in this community service activity is Community Education through Legal Counseling with a Participatory Action Research (PAR) approach. The PAR method was selected because it emphasizes collaboration and active engagement between researchers and participants, viewing research as a process "from, by, and by, for the community." The legal counseling, delivered by lecturers from the Faculty of Law, Universitas Sultan Ageng Tirtayasa, was conducted interactively through group discussions and question-and-answer sessions, enabling the community not only to receive information unidirectionally but also to actively formulate solutions to bureaucratic challenges they encounter. The results of the activity demonstrate a significant improvement in the legal literacy of both the community and village officials concerning their rights and obligations in licensing services. This participatory approach successfully fostered collective awareness to oversee information transparency and service accountability, thereby minimizing discretionary practices and strengthening the institutional legitimacy of village governance.